2022
DOI: 10.3389/fpsyg.2022.1000109
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical exercise and mobile phone addiction among Chinese college students: Testing mediation and moderation effects

Abstract: BackgroundDuring the COVID-19 pandemic, suspensions of activities and long periods of self-isolation led to a sharp increase in excessive use of mobile phones, which sparked public concern about mobile phone addiction (MPA). In recent years, more and more attention has been paid to physical exercise as a protective effect of MPA. However, more studies are needed to reveal this relationship and the exact mechanisms, based on which this study tested the mediating and moderating roles of self-control, rumination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 139 publications
0
13
0
Order By: Relevance
“…On the contrary, he/she would give more meaning to his/her life and continue to improve himself/herself, thus greatly mitigating the risk of mobile phone addiction. 33 This is why the sense of meaning in life fully mediates the effect of mindfulness training on mobile phone addiction in this study.…”
Section: Discussionmentioning
confidence: 75%
“…On the contrary, he/she would give more meaning to his/her life and continue to improve himself/herself, thus greatly mitigating the risk of mobile phone addiction. 33 This is why the sense of meaning in life fully mediates the effect of mindfulness training on mobile phone addiction in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Rumination significantly mediated the antidepressant effects of both Bikram yoga and aerobic exercise ( La Rocque et al, 2021 ). A close relationship is found between physical exercise and rumination, where rumination served as an independent mediating variable in the association between physical exercise and mobile phone addiction ( Zeng et al, 2022 ). A randomized controlled trial revealed that the mechanism by which physical activity therapy affects depression maybe mediated by rumination, self-esteem, and memory bias ( Schmitter et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary benefit of exercise is that it allows individuals to detach themselves from the online environment and engage in dynamic activities in the real world, shifting the focus of their attention and facilitating face-to-face social interactions with others. Furthermore, exercise can enhance self-control as a way to reduce dependence on smartphones ( Zhong, Wang & Zhang, 2021 ; Zeng et al, 2022 ; Zhang et al, 2022 ), while contributing to the treatment of a range of physical and psychological symptoms caused by excessive smartphone use. Unfortunately, the current literature gap revealed that we know little about the impact of PA on PSU in other domains, except for physical exercise in leisure time, which can be a good entry point for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reduction of individual inhibitory control caused a decrease in motivational seeking and suppression of desire, which resulted in excessive addictive behavior, according to the Interaction of Person-Affect-Cognition-Execution (I-PACE) model for addictive behaviors ( Brand et al, 2016 , 2019 ). Exercise was one way to enhance inhibitory control ( Fan et al, 2021 ), and Zeng et al (2022) and Zhang et al (2022) found that exercise could indirectly affect PSU through self-control. It was practicable to move away from the immediate hedonism of PSU by using capacity-enhancing strategies targeted at improving individuals’ self-discipline and rational management ( Busch & McCarthy, 2021 ).…”
Section: Introductionmentioning
confidence: 99%